Literature Review: Analisis Faktor-faktor yang Berhubungan dengan Kejadian Anemia Pada Remaja Putri - Iwan Abdi Suandana; Malinda Capri Nurul Satya; Lisus Setyowati; Dian Kartika Sari; Stephani Nesya Renamastika (Puslitbang Sinergis Asa Professional, 2022)
Anemia is a medical condition in which the hemoglobin level less than normal. Normal Hb levels in adolescent girls are >12 g/dl. Anemia in adolescent girls is still relatively high. Impact of anemia can be caused the body to become thin and drastically lose weight, shortness, constant illness, and anemia. This literature review identified factors that are consistently associated with the incidence of anemia in adolescent girls. This research method is a literature review by collecting various databases from Pubmed, Science Direct, Proquest, and Google Scholar. The selection of articles were limited from 2014-2019 and 20 articles were found. Factors that are consistently associated with the incidence of anemia in adolescents girls include the level of knowledge of girl adolescents regarding anemia, iron intake, nutritional status and the duration of menstruation, BMI, category of residence (rural/urban), dietary habits, and infections such as malaria. It is necessary to provide continuous blood supplement tablets to young women from the government and schools so that they can meet their nutritional needs and further research is expected to be able to use different research designs such as case control and cohorts in order to prove a stronger causal relationship, this is because there have been quite a number of studies related to risk factors for the incidence of anemia in adolescent girls.